Smart Crime Prevention in Smart City Tinjauan Pemetaan dan Rekomendasi Penerapan Sistem untuk Mendukung Smart Living di Banjarmasin Smart City - Saberan; Subandi; Aulia Akhrian Syahidi (Prosiding SISFOTEK, 2023)
Crime in Indonesia, especially in Banjarmasin City, shows a decline between 2020-2022. However, the government must still be vigilant and maintain the safety of citizens from crime, especially in the context of its commitment to realizing a Smart City. Technological advances in Smart Cities also bring new challenges such as increased crime and security risks. This research aims to carry out mapping related to Smart Crime Prevention in the Smart City context to recommend a Smart Crime Prevention system that supports the Smart Living program in Banjarmasin Smart City. The method used is Mapping Review, which involves stages including determining research questions, selecting relevant reference sources, identifying appropriate keywords, carrying out filtering based on inclusion and exclusion criteria, and extracting and synthesizing relevant data. The results of this mapping show that the technology used in Smart Crime Prevention includes Computer Vision, Digital Image Processing, Internet of Things, Closed Circuit Television, Global Positioning System, Embedded Systems, Cloud Computing, Sensors, Big Data, Data Mining, and Artificial Intelligence. Its application includes urban environments, homes, roads, traffic, women’s safety against sexual harassment, and fire hazards and other threats. We recommend that Banjarmasin as a city that is realizing a Smart City must utilize these technologies and appropriate algorithms to minimize crime and keep citizens safe. This is important in supporting the Smart Living program in Banjarmasin City.